Phylogenetic analysis of sigmodontine rodents (Muroidea), with especial reference to the akodont genus Deltamys - D'Elía, G. (2003)
We present a comprehensive phylogenetic analysis based on cytochrome b gene sequences of sigmodontine rodents. Our particular interest is to estimate the phyletic position of Deltamys, a taxon endemic to a small portion of the La Plata river basin in Argentina, Brazil, and Uruguay, and to assess its generic status. The three primary conclusions derived from our analyses are: (1) cotton rats (Sigmodon) are the sister group of the remaining sigmodontines, (2) the tribe Akodontini is monophyletic with moderate support, and (3) Deltamys falls outside of a clade containing all species of subgenera of Akodon yet examined, and thus we grant Deltamys status of full genus.